2012
DOI: 10.3324/haematol.2011.061507
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intratumoral B cells with rituximab in addition to CHOP in angioimmunoblastic T-cell lymphoma. A clinicobiological study of the GELA

Abstract: The online version of this article has a Supplementary Appendix. BackgroundIn angioimmunoblastic T-cell lymphoma, symptoms linked to B-lymphocyte activation are common, and variable numbers of CD20 + large B-blasts, often infected by Epstein-Barr virus, are found in tumor tissues. We postulated that the disruption of putative B-T interactions and/or depletion of the Epstein-Barr virus reservoir by an anti-CD20 monoclonal antibody (rituximab) could improve the clinical outcome produced by conventional chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 45 publications
5
62
4
1
Order By: Relevance
“…The trial did not proceed to the 2 nd stage of recruitment as the CR rate was less than the pre-defined threshold of 40%. The CR rate was inferior to that reported with CHOP with or without rituximab [2,6] and remissions were short lived with a median PFS of 5.5 months.…”
Section: Partial Response N=3 (20%) Progressive Disease Occurred In mentioning
confidence: 42%
See 1 more Smart Citation
“…The trial did not proceed to the 2 nd stage of recruitment as the CR rate was less than the pre-defined threshold of 40%. The CR rate was inferior to that reported with CHOP with or without rituximab [2,6] and remissions were short lived with a median PFS of 5.5 months.…”
Section: Partial Response N=3 (20%) Progressive Disease Occurred In mentioning
confidence: 42%
“…The median age at presentation is 62-70 years and 80-90% of patients have advanced stage disease [2][3][4][5][6]. It typically follows an aggressive course with poor prognosis; although complete remission (CR) is achieved in 44-61% of patients, relapses are frequent and the median overall survival (OS) is approximately 3 years with 5-year survival of 32% [2,3,6]. Due to its low incidence, there have been few prospective clinical trials in AITL and most data informing treatment strategies are derived from retrospective and registry studies.…”
Section: Aitl Is a Rare Disease Accounting For 1-2% Of Non-hodgkin Lymentioning
confidence: 99%
“…To test this hypothesis, the GELA group recently designed a clinical trial including rituximab in the treatment of AITL. Even though a preliminary analysis suggested a beneficial effect from the addition of rituximab, the final results did not confirm it [16]. Nonetheless, a functional role of B-cells in the pathogenesis of the disease could not be completely ruled out and further functional studies would be warranted.…”
Section: Molecular Pathology Of Alclmentioning
confidence: 63%
“…In particular, as they are provided with diverse prognosis [4][5][6], different phenotypic and molecular profiles [6][7][8][9][10], and distinct genetic patterns [11][12][13][14][15], it is reasonable that in the near future ad hoc interventions will be adopted. In this regard, very recently Brentuximab Vedotin, a conjugated anti-CD30 monoclonal antibody (MoAb) was approved for the treatment of relapsed/refractory ALCL but not other PTCL subtypes, while clinical trials have been designed for specific subtypes [16], many of which are currently ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…To target tumor-infiltrating B cells, newly diagnosed AITL was treated with a combination of rituximab plus CHOP (R-CHOP) in a clinical trial, although the benefit of rituximab was not demonstrated. 90 Some AITL patients responded to immunosuppressive agents, including cyclosporin A and corticosteroids 91 . These agents may contribute to the suppression of autoimmune-like manifestations, and to the regression of tumors.…”
Section: Treatment Options For Aitlmentioning
confidence: 99%